(untitled) (Journal of actual problems of jurisprudence, 2015)
This article deals with the correlation between the concepts «tourism» and «tourist activity» under the laws of the Republic of Kazakhstan. In par ticular, it analyzes characteristics of tourism and tourist activities. Tourist activity is considered as an entrepreneurial activity. The attention is given to the features of tourist activity as entrepreneurial activity. Also the issue of subjects of tourist activity are analyzed.